2008
DOI: 10.1038/oby.2007.37
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Relationship Between Body Composition and Patella Cartilage in Healthy Adults

Abstract: background: Although obesity is a risk factor for patellofemoral osteoarthritis (OA), it is unclear whether the components of body composition, such as muscle and fat mass, are major determinants of articular cartilage properties at the patella. objective: The aim of this study was to determine whether anthropometric and body composition measures, assessed over 10 years, were related to articular patella cartilage volume and defects in healthy adults with no clinical knee OA. Methods and Procedures: Two hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 30 publications
1
28
0
2
Order By: Relevance
“…Most studies examined obesity in the context of an increased BMI, without any distinction between adipose and non-adipose body mass [45][46][47][48][49][50]. Considering the above, we utilized FT as an indirect body fat content index.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies examined obesity in the context of an increased BMI, without any distinction between adipose and non-adipose body mass [45][46][47][48][49][50]. Considering the above, we utilized FT as an indirect body fat content index.…”
Section: Discussionmentioning
confidence: 99%
“…There are many theories on t h e e t i o l o g y o f t h e g r e a t e r i n c i d e n c e o f patellofemoral injuries in females 21) . Teichtahl et al 22) reported that increased anthropometric measures of obesity, as well as fat mass, are associated with increased risk of patellofemoral injury for both males and females; particularly females, who have greater baseline body mass, and appear to have an increased risk for the onset and progression of patellofemoral injury 22) .…”
Section: Discussionmentioning
confidence: 99%
“…Patella cartilage volumes and defects were investigated using magnetic resonance images (Hanna et al, 2006;Kessler et al, 2006;Hanna et al, 2007;Teichtahl et al, 2008;Wijayaratne et al). Computed tomography is an effective diagnostic modality for 2D multiplanar images of bone structures, including their defects.…”
Section: Discussionmentioning
confidence: 99%